Aposentadoria de militares: construindo novas perspectivas - Cantarelli, Adriane Scheffer (2020)
This study aimed to understand the experience of military servants regarding the transition period between the end of active life and the beginning of retirement. Being considered a qualitative, descriptive study. The research was carried out in an army military unit in the city of Santa Maria, RS. The research participants were 16 military men close to 50 years old and the production of data occurred through an individual questionnaire and focus group. Four meetings were held, chosen from the literature review, always addressing themes relevant to the phase of the life cycle that the military are in. The topics covered were the following: Introduction to the aging process, II-Presentation of the Preparation programs for retirement (PPAs) of federal, civil servants. III-Report of concrete experiences of military personnel who passed to the reserve, reporting their choices, their current reality and the application of the research instruments. As a work option, we use the focus group technique, when themes are addressed and discussed in groups and the Brazil Old age Schedule questionnaire (section I). Sixteen military personnel participated in the study and intervention, 5 years from the end of their active life, with different ages and patents. We conclude that there is an interest by the majority of the military in developing a type of activity after their transition to the reserve, however the way that the participants hope to be able to enjoy their retirement presented differences between the participants, and that the military that are in the process of preparing for retirement. reservation, they are already worrying about their daily occupations, but they reported that some type of preparation is important when they are still working.